Profil Usaha Industri Kecil Tahu dan Tempe “Makmur Jaya” di Kecamatan Denpasar Barat, Kota Denpasar - AMBARA, KENTAK YULI; USTRIYANA, I NYOMAN GEDE; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 2 (2017), 2017)
Profile of Small Industries Tofu and Tempeh “Makmur Jaya” in The District West Of Denpasar, The City Of Denpasar This study aimed to determine the profile of industrial businesses of tofu and tempeh (Makmur Jaya), which included the availability of raw and auxiliary materials, production systems, production processes, types and quantities of production, costs of production, revenue, and marketing channels of small industries in the District of West Denpasar, Denpasar City. The data collected in this study were primary and secondary data, and method of collecting data. Profile of small industries of tofu and tempeh is a general overview of a business, in this case is the business of tofu and tempeh. The source of capital used by Makmur Jaya in producing tofu and tempeh was its own capital for business sustainability. The average amount of soybean raw materials required by Makmur Jaya in one production process for the manufacture of tofu and tempeh, namely, a total of 1.75 quintals per day to produce tofu and tempeh. Of which 75 kg of soybeans were used for making tofu, while the remaining100 kg for making tempeh. The average cost of production facilities issued by Makmur Jaya for producing tofu and tempeh for one time production process was an average of Rp. 59,762,083 per month. Makmur Jaya generally marketed their products to markets. The revenue generated by Makmur Jaya industrial business of tofu and tempeh was Rp 39,237,917 per month.
Keywords: tofu and tempeh; profiles; marketing channel; revenue